A közszolgálati jog kodifikációja mint az állami válságkezelés eszköze: a német történeti példa - Sallai, Balázs (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
The central thesis of this article is that the codification of public service law in a uniform code (service pragmatics) is important not only from the narrow perspective of jurisprudence, but also from the perspective of power politics. Among these mechanisms of exercising power, the text focuses specifically on the issue of state crisis management, for which I attempt to analyze positive and negative examples from 19th- and 20th-century German (legal) history.